Methods in plant foliar volatile organic compounds research1. (15th December 2015) - Materić, Dušan; Bruhn, Dan; Turner, Claire; Morgan, Geraint; Mason, Nigel; Gauci, Vincent
Abstract : Plants are a major atmospheric source of volatile organic compounds (VOCs). These secondary metabolic products protect plants from high‐temperature stress, mediate in plant–plant and plant–insect communication, and affect our climate globally. The main challenges in plant foliar VOC research are accurate sampling, the inherent reactivity of some VOC compounds that makes them hard to detect directly, and their low concentrations. Plant VOC research relies on analytical techniques for trace gas analysis, usually based on gas chromatography and soft chemical ionization mass spectrometry. Until now, these techniques (especially the latter one) have been developed and used primarily by physicists and analytical scientists, who have used them in a wide range of scientific research areas (e.g., aroma, disease biomarkers, hazardous compound detection, atmospheric chemistry). The interdisciplinary nature of plant foliar VOC research has recently attracted the attention of biologists, bringing them into the field of applied environmental analytical sciences. In this paper, we review the sampling methods and available analytical techniques used in plant foliar VOC research to provide a comprehensive resource that will allow biologists moving into the field to choose the most appropriate approach for their studies.